2015
DOI: 10.1021/acs.energyfuels.5b00286
|View full text |Cite
|
Sign up to set email alerts
|

Methane Adsorption Capacities of the Lower Paleozoic Marine Shales in the Yangtze Platform, South China

Abstract: The adsorption capacities of the Lower Silurian Longamxi and Lower Cambrian Niutitang marine shales in the Yangtze Platform in China were investigated through methane adsorption experiments. The correlations between the adsorption capacities and major factors, e.g., total organic carbon (TOC) contents, thermal maturity, mineral composition, moisture content, pressure, and temperature, were discussed. The isosteric adsorption heat was calculated according to the temperature dependency of the methane adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Such a pattern is quite analogous to previous studies (e.g. Ji et al, 2015;Wu et al, 2015) and is of great significance for understanding the changes in gas adsorption capacity of organic-rich shales.…”
Section: Shale Gas Adsorption Capacitysupporting
confidence: 86%
See 2 more Smart Citations
“…Such a pattern is quite analogous to previous studies (e.g. Ji et al, 2015;Wu et al, 2015) and is of great significance for understanding the changes in gas adsorption capacity of organic-rich shales.…”
Section: Shale Gas Adsorption Capacitysupporting
confidence: 86%
“…Shale gas is stored in three different types of geological environment and they are (1) free gas in pores and fractures, (2) adsorbed gas in organic matters and clay minerals, (3) dissolved gas in residual oil and water (Zhang et al, 2012;Hao et al, 2013;Rexer et al, 2013;Ji et al, 2015;Wu et al, 2015;Chen et al, 2017a,b). Free gas and adsorbed gas are predominant in high-maturity shales (Hao et al, 2013).…”
Section: Shale Gas Adsorption Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lack of vitrinite in these early Paleozoic marine shales, vitrinite reflectance (Ro) was calculated from the measured pyrobitumen reflectance (Rb) on the basis of their arithmetic relationship of Ro ¼ 0.3195 þ 0.6790Rb (Wu et al, 2015).…”
Section: Toc and Romentioning
confidence: 99%
“…In shale gas reservoirs, CH 4 is generally stored in three different states, which is claried as free-gas state in nanopores, absorbed-gas state in kerogen, and adsorbed-gas state on pore surface. [3][4][5] It has been found that the adsorbed CH 4 can take 20-85 vol% accounting for the total gas amount. 4 Recently, extensive studies are implemented to measure the CH 4adsorption on shale samples.…”
Section: Introductionmentioning
confidence: 99%